MENINGKATKAN KETERAMPILAN MENYIMAK DENGAN METODE BERCERITA MELALUI MEDIA BONEKA JARI - Nopriani, Yosi; Saparahayuningsih, Sri; Yulidesni, Yulidesni (Jurnal Ilmiah Potensia, 2018)
The problem of this research was whether storytelling method through finger puppets media can improve students’ listening skill. The aim of this classroom action research was to improve listening skill of early childhood students by using storytelling method with finger puppets media. The subject of this research was group B3 students with the total of 15 people consisted of 8 female students and 7 male students. The type of the research used in this study was classroom action research consisted of 2 cycles with 3 meetings for each cycle. This research used observation as the data collection technique. The technique of analyzing the data was done by using mean score, indicator of success for learning mastery, and t-test. The research result showed that storytelling method by using finger puppets can improve the students’ listening skill, it was gotten the mean score of students’ listening skill was 4.37 or in a good criteria, with learning mastery of 86% and it was significantly proven from t-test calculation between the cycles which was 5.66 ? ttable, both for significance level of 5% = 2.16 and 1% = 2.98. The suggestion for teachers is that storytelling method by using the media of finger puppets, stick puppets, string puppets, hand puppets, and sticky puppets was an alternative that can be used to improve students’ listening skill.